The Return of the Silenced: Aboriginal Art as a Flagship of New Australian Identity - Elżbieta Wilczyńska (Anglica. An International Journal of English Studies)
The paper examines the presence of Aboriginal art, its contact with colonial and federation Australian art to prove that silencing of this art from the official identity narrative and art histories also served elimination of Aboriginal people from national and identity discourse. It posits then that the recently observed acceptance and popularity as well as incorporation of Aboriginal art into the national Australian art and art histories of Australian art may be interpreted as a sign of indigenizing state nationalism and multicultural national identity of Australia in compliance with the definition of identity according to Anthony B. Smith.